Mental health self-stigma: links with social self-worth contingencies and ally support - Rebecca A. Burwell; Sierra Bias (Cogent Mental Health)
Self-stigma (also known as internalized stigma) is common among individuals with mental illness, though less is known about its risk factors. We propose that social self-worth contingencies (over-reliance on others’ approval to maintain self-worth) confer risk for self-stigma, and that community connectedness and ally support build resilience against it. The current study investigates links between self-worth contingencies, community/ally support, and self-stigma among 96 undergraduates (MAge = 20.33, SD = 1.66) from a medium-sized state university who self-reported one or more mental health conditions. We propose that community/ally support mediate the association between self-worth contingencies and self-stigma. Results support hypothesized correlations between social self-worth contingencies, ally support (participant-defined), and self-stigma, though do not support links with community connectedness or researchers’ definition of ally support. Participant-defined ally support predict self-stigma, controlling for self-worth contingencies, though do not meet all conditions for mediation. Rather, self-worth contingencies and ally support independently predict self-stigma. Participants’ descriptions of stigma and suggestions for addressing it are presented. Results have implications for prevention/intervention by addressing self-worth contingencies and fostering ally support, supporting a multi-prong (individual and community) approach to reduce self-stigma.